Effects of plant growth regulators on quality flower and seed production of marigold (Tagetes erecta L.) - Kumar, Parveen; Singh, Arvinder; Laishram, Nomita; Pandey, RK; Dogra, Sheetal; Jeelani, M Iqbal; Sinha, BK (Bangladesh Journal of Botany, 2020)
Effects of different growth regulators and their application time on production of quality flower and seed production of marigold (Tagetes erecta L.) were investigated. Experimental factors include nine foliar applications of growth regulators viz., Control (no application), two doses each of GA3, salicylic acid, benzyl adenine, cycocel, and two application times viz., (i) application at 25 DAT, (ii) application at 50 DAT. Results suggest that foliar spray of 250 ppm gibberellic acid enhanced growth, and improved seed yield and quality parameters of marigold. Among the times of application tested, it was observed that application at 25 days after transplanting (DAT) gave superior values for all the flower and seed parameters under study.